Plasma interleukin-7 correlation with human immunodeficiency virus RNA and CD4+ T cell counts, and interleukin-5 with circulating hepatitis B virus DNA may have implications in viral control - Vimali, Jaisheela; Yong, Yean Kong; Murugesan, Amudhan; Vishnupriya, Kumaran; Ashwin, Rajeev; Daniel, Evangeline Ann; Balakrishnan, Pachamuthu; Raju, Sivadoss; Rosmawati, Mohamed; Velu, Vijayakumar; Larsson, Marie; Shankar, Esaki M. (Frontiers in Medicine, 2022)
Chronic viral infections represent a leading cause of global morbidity and mortality. Chronic HBV, HCV, and HIV infections result in cytokine perturbations that may hold key implications in understanding the complex disease mechanisms driving virus persistence and/or resolution. Here, we determined the levels of various plasma cytokines using a commercial Bio-Plex Luminex cytokine array in chronic HBV (n = 30), HCV (n = 15), and HIV (n = 40) infections and correlated with corresponding plasma viral loads (PVLs) and liver parameters. We observed differential perturbations in cytokine profiles among the study groups. The cytokines levels positively correlated with PVL and liver transaminases. The monocyte-derived cytokines viz., MIP-1β, IL-8, and TNF-α, and Th2 cytokines like IL-4, IL-5, and IL-13 showed a better correlation with liver enzymes as compared to their corresponding PVLs. Our investigation also identified two cytokines viz., IL-5 and IL-7 that inversely correlated with HBV DNA and HIV PVLs, respectively. Regression analysis adjusted for age showed that every increase of IL-5 by one unit was associated with a reduction in HBV PVL by log10 0.4, whereas, every elevation by a unit of IL-7 was associated with decreased HIV PVL by log10 2.5. We also found that IL-7 levels correlated positively with absolute CD4+ T cell counts in HIV-infected patients. We concluded that plasma IL-5 and IL-7 may likely have a key role on viral control in HBV and HIV infections, respectively. A noteworthy increase in cytokines appears to bear protective and pathological significance, and indeed is reflective of the host’s versatile immune armory against viral persistence.